Pengaruh Employee Engagement terhadap Job Performance melalui Creativity sebagai Variabel Mediasi - Agil Rasul Baharsyah; Dwiarko Nugrohoseno (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The purpose of this paper is to explore the relationship between employee engagement and job performance and to test whether creativity mediates the relationship between engagement and job performance. Job performance is the result of contributions made by employees to the company. Previous research found that employee engagement and creativity were the strongest predictors of job performance. Therefore, the research here wants to test whether creativity is a mediator variable of the two constructs. The sample in this study amounted to 96 banking employees in Sumenep Regency using the snowball sampling method in data collection. The results of the model equation test show that employee engagement has no significant effect on job performance. Employee engagement has a significant effect on creativity. Creativity has a significant effect on job performance. In addition, creativity as a mediator variable has a significant effect on the relationship between employee engagement and job performance. Employee engagement is not directly related to job performance but is mediated by creativity. The managerial implication of the results of this study is that banking companies can review the factors that can hinder or reduce their employee engagement to maintain the employee's job performance.